A retrospective study on treatment for postburn contracture of axilla with propeller flap cover at a tertiary care center - Kabita Kalita; Swamy Vivek Gurindagunta; M Nithin (Wolters Kluwer Medknow Publications, 2022)
Background: The gold standard for burn scar reconstruction is to utilize adjacent skin flaps for the ease of operation and to match the skin characteristics. The objective of this study is to share our experiences using propeller flap cover for "postburn contracture of axilla (PBCA)" release reconstruction. Materials and Methods: This 5-year retrospective observational study was undertaken in the Plastic Surgery Department of GMCH, Guwahati, from 2016 to 2020 with the data available after obtaining the Ethics Committee approval. The patient records and photographs were gathered from the Medical Records and the Plastic Surgery Department of GMCH, Guwahati, respectively. Patients treated with a propeller flap cover were scrutinized. Results: The patients operated for PBCA were 36. There were 12 males and 14 females with a mean age of 21 years. Twelve patients with spared axillary dome skin underwent a central axis subcutaneous pedicle propeller flap. The flaps had dimensions of 8-12 cm in length and 6-9 cm in width. The pedicle was approximately 2-2.5 cm in diameter. The few complications seen included wound dehiscence and delayed wound healing, edge hypertrophy, band contractures, marginal necrosis, and pin cushioning. During follow-up, no recontractures were seen. Conclusions: We conclude that central axis subcutaneous pedicle propeller flap is a simple and effective treatment for mild-to-moderate PBCA with spared axillary dome skin. These flaps provide durable soft tissue cover with enhanced flap survival, functional mobility, and esthetics.